2022
DOI: 10.1177/21582440221094601
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Principal Leadership Style and Student Achievement: A Comparative Study between Germany and China

Abstract: This article explored the different clusters of leadership styles and the relationship between principal leadership style and student academic achievement in domains of mathematics, reading, science, and collaborative problem-solving in Germany and China. We used PISA 2015 data covering 6,504 students and 256 school principals from German schools and 9,841 students and 268 school leaders from Chinese schools. Results identified three leadership styles in Germany, namely, transformational (23.4%), instructional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 115 publications
0
6
0
Order By: Relevance
“…Knowing the composite parts of collective academic optimism has the added benefit of suggesting a wider set of techniques for boosting optimism within the school. This is a benefit that adds to the overall value of having this knowledge (Chen, Ning & Bos, 2022). The leaders of the school have three different options available to them: they may either boost the academic emphasis, improve the collective efficacy, or enhance the trust that the faculty has in the student and their parents.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Knowing the composite parts of collective academic optimism has the added benefit of suggesting a wider set of techniques for boosting optimism within the school. This is a benefit that adds to the overall value of having this knowledge (Chen, Ning & Bos, 2022). The leaders of the school have three different options available to them: they may either boost the academic emphasis, improve the collective efficacy, or enhance the trust that the faculty has in the student and their parents.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…However, contingency theorists thought that the leader was the main focus of the leader-subordinate interaction, despite the fact that they thought that employees played a significant part in defining the leader-subordinate relationship. Although the contingency approach still places a lot of emphasis on the leader, it also emphasises the importance of group dynamics (Chen, Ning & Bos, 2022). Some of our current concepts of group dynamics and leadership have been developed as a result of these examinations into the interactions between groups and their leaders.…”
Section: Conceptual Developmentmentioning
confidence: 99%
“…The study found a strong and positive correlation between the principal autocratic leadership style and teacher job performance in Faisalabad city. Chen et al (2022) compared the relationship between principal leadership style and student achievement in Germany and China. They found significant differences between leadership styles adopted in Germany and China.…”
Section: Literature Reviewmentioning
confidence: 99%